MANAJEMEN SAMPAH PADAT DI KOTA BANDUNG DAN METODE ALTENATIF PENGOLAHANNYA - Sunasih Mulianingsih (GoAcademica Research dan Publishing, 2019)
The problem of mucipal waste management in the city of Bandung has been an unsolved problem to date. The rapid population growth plus many new arrivals to the city of Bandung have increased waste production from year to year. According to the Department of Environment and Sanitation, the city of Bandung produces around 1477 metric tons of solid waste per day, of which 63% is organic matter. Garbage collection in the city of Bandung is managed by the city government through the BUMD which handles it. About 44.3% of solid waste management in Bandung city is composted to produce fertilizer material, 54.7% is rejected and dumped in landfills. 23% of non-organic waste is mostly recycled and around 11.3% is taken to landfills, while 14% of residual waste such as B3 is dumped. This investigation also includes an analysis of the economic benefits that can be realized by implementing incineration and a discussion of the challenges faced in the city of Bandung to implement changes to the existing urban solid waste management system.